The Relationship Between Body Image, Diet Quality, and Physical Activity with Nutritional Status in Adolescent Girls at SMPN 3 Meulaboh in 2024 - Nabila, Cindy; Harahap, Laila Apriani; Febriansyah, M Irfan; Muliadi, Teuku; Muhsin, Sri Wahyuni (Journal of Nutrition Science, 2025)
Adolescents in Indonesia face three nutritional burdens: undernutrition, overnutrition, and micronutrient deficiencies. The 2023 Indonesian Health Survey found that Aceh Province ranked 14th in terms of prevalence of nutritional status among adolescents aged 13-15 years. Factors such as body image, diet quality, and physical activity play an important role in determining the nutritional status of adolescent girls. This study aims to analyze the relationship between body image, diet quality, and physical activity with nutritional status in adolescent girls at SMPN 3 Meulaboh. This study used a quantitative approach with a cross-sectional design using chi-square analysis. The study sample consisted of 162 adolescent girls selected using proportionate stratified random sampling techniques. The results of the study showed that there was no significant relationship between body image and nutritional status (p-value = 0.814), there was a significant relationship between diet quality based on nutritional adequacy figures and nutritional status (energy p-value = 0.006), (protein p-value = 0.003), (fat p-value = 0.006), (carbohydrate p-value 0.027), there was a significant relationship between physical activity and nutritional status (p-value = 0.013). In this study, it can be concluded that diet quality and physical activity have a significant relationship with the nutritional status of adolescent girls. Body image does not have a significant relationship with the nutritional status of adolescent girls.